A test of Hebb's postulate at identified synapses which mediate classical conditioning in Aplysia - Carew, TJ (J Neurosci, 1984)
In 1949, D. O. Hebb proposed a novel mechanism for producing changes in the strength of synapses that could account for associative learning. According to Hebb , the strength of a synapse might increase when the use of that synapse contributes to the generation of action potentials in a postsynaptic neuron. Thus, an essential feature of this postulate is that action potentials must occur in both a postsynaptic cell and a presynaptic cell for associative synaptic changes to occur. We have directly tested Hebb 's postulate in Aplysia at identified synapses which are known to exhibit a temporally specific increase in efficacy during a cellular analogue of differential conditioning. We find that the mechanism postulated by Hebb is neither necessary nor sufficient to produce the associative change in synaptic strength that underlies conditioning in Aplysia. In contrast, impulse activity in the presynaptic cell must be paired with facilitatory input, supporting the hypothesis that the temporal specificity of classical conditioning in Aplysia can be accounted for by activity-dependent amplification of presynaptic facilitation.